Predictive torque control of electric vehicle - Mohammed El Amin Abdelkoui; Abdeldjebar Hazzab (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The following article represents the development of a traction system of an electrical vehicle (EV) that consist of two Three-phase squirel-cage induction motors (IM) that permit the drive of the two front driving wheels. The two motors are controlled  using the Predictive Torque Control (PTC) method; A technique based on the next step prediction and evaluation of the electromagnetic torque and stator flux In a cost function in order to determinate the inverter switching vector that minimize the error between references and predicted values. PTC is what we tried to underline in this paper, so we explain below the principle of the method; and the system mathematical description is provided. An electronic differential is applied on the system to control independently the speed of the two wheels at different operating conditions in order to characterize the driving wheel system behavior, the robustness in steady state and in transient state.